2009
DOI: 10.1016/j.psychres.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control: Relation to schizophrenia, to recovery, and to depression and psychosis — A 15-year longitudinal study

Abstract: Purpose-The present prospectively designed 15-year longitudinal research was conducted to study whether locus of control is linked to diagnosis, to major symptoms, to functioning and recovery, and to personality for schizophrenia patients, depressive patients, and patients with other major disorders.Procedure-The research studied 128 patients from the Chicago Follow-up Study at the acute phase and reassessed them 5 times over a 15-year period. Patients were evaluated on locus of control, global outcome, recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 50 publications
(68 reference statements)
5
71
0
1
Order By: Relevance
“…The data tend to support much of the research done on locus of control and depression, which generally indicates that externality, is linked to depression [10]. While understanding the relationship between these two constructs (Depression and Externality in Locus of Control) which are so closely studied in literature, it is difficult to state the cause and effect [9]. In another study [11], the focus was on correlation of depression, age and locus of control.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…The data tend to support much of the research done on locus of control and depression, which generally indicates that externality, is linked to depression [10]. While understanding the relationship between these two constructs (Depression and Externality in Locus of Control) which are so closely studied in literature, it is difficult to state the cause and effect [9]. In another study [11], the focus was on correlation of depression, age and locus of control.…”
Section: Introductionmentioning
confidence: 61%
“…The relation between a more external locus of control and increased depression has been supported by studies examining college students [16], cancer patients [17]. In the longitudinal study by Harrow and others [9], the relation between Locus of Control and Depression was significant for the overall sample (t = 2.54, 124 df, p = .01) indicating that patients who were more External in their Locus of Control at the 4.5-year follow ups were likely, concurrently, to be more depressed, while those patients who were more Internal on Locus of Control were likely, concurrently, to be less depressed at the 4.5 year follow. The present study was limited by a small sample size and further studies in this direction are warranted.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…32 A study of 161 patients with severe mental illness (schizophrenia, BD and depression) found a strong association between empowerment and recovery, 115 and a longitudinal study of 128 patients with a diagnosis of schizophrenia found that internal locus of control was associated with long-term recovery. 116 Studies of predictors of recovery using more traditional psychiatric definitions focused on symptom remission or non-recurrence have found that neuropsychiatric factors are relevant. For example, a study on 436 patients with schizophrenia spectrum diagnoses 117 found that better insight was associated with good outcomes (defined as a single episode with no persistent symptoms); however, other evidence suggests that increasing insight is often associated with poor outcomes such as greater suicidality in people with psychosis.…”
Section: Introductionmentioning
confidence: 99%